خوێندنەوەیەكی تیۆری بۆ پەیوەندی هاوسەران توێژینەوەیەكی وەسفی شیكارییە - نصرالله, سه‌رپه‌رشتیار: پ.ی.د. واحدە حمە وەیس; صاڵح, توێژه‌ر: دڵگەش كریم (Sulaimani Journal for Humanities, 2023)
This research is a theoretical analysis. It aims to find out the causes behind the weakness or strength of marital relationships. It also analyses the relation between spouses according to the theory of social exchange because a suitable and healthy relationship between spouses is necessity of every family due to the role of spouses in families and society in general. The researcher wants to find out about the relationship between spouses because it is a modern topic and is the basis of a proper family. This relationship is founded upon rights and duties and it has been there for a long time; however, this has changed due to scientific and technological developments. These changes have had effects on the spouses and their relationship. The social exchange theory looks at this relationship as balanced or not balanced. Accordingly, there will be a strong relationship if each person undertakes his/her responsibilities and puts aside his/her personal interests. Thus they will attain a comfortable and happy relationship.